Pie & Whiskey : writers under the influence of butter & booze - Lebo, Kate; Ligon, Samuel (Sasquatch Books, 2017)
"Pie & Whiskey is the tent revival of literary events where writers such as Anthony Doerr, Steve Almond, and Elissa Washuta present original works based on prompts that include the words pie and whiskey. This anthology collects the best of that writing along with new pieces to bring this spirited gathering to the printed page. Pie & Whiskey, the book, is a literary collection of readings presented over the past six years in Spokane, WA, and Missoula, MT, at Pie & Whiskey, the event, run by Kate Lebo and Samuel Ligon. Writers like Jess Walter, J Robert Lennon, Kim Barnes, and ML Smoker were invited to generate new work based on prompts that involve pie or whiskey or both. Sam and Kate figured that good writing served with a slice of pie and a shot of whiskey would create an energized atmosphere uncommon at literary events. The contributors, drawn mainly from the west, but not exclusively, responded with surprising, funny, heartbreaking, fantastically written stories and poems. The book will include a smattering of pie recipes and whiskey-centric cocktails. Look here for tasty literary servings"--